Peptide stapling techniques based on different macrocyclisation chemistries. (8th September 2014) - Lau, Yu Heng; de Andrade, Peterson; Wu, Yuteng; Spring, David R.
Abstract : This review analyses how the choice of macrocyclisation chemistry can influence the biological properties and applications of stapled peptides. Abstract : Peptide stapling is a strategy for constraining short peptides typically in an alpha-helical conformation. Stapling is carried out by covalently linking the side-chains of two amino acids, thereby forming a peptide macrocycle. There is an expanding repertoire of stapling techniques based on different macrocyclisation chemistries. In this tutorial review, we categorise and analyse key examples of peptide stapling in terms of their synthesis and applicability to biological systems.